Taking the Mystical Ways toward Allah: Kyai Sholeh Darat Al-Samarani’s Perspective - Marsuki Marsuki; M Zainuddin; Achmad Khudori Soleh (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2023)
For a servant, taking the mystical way to get closer to Allah is necessary to achieve perfection in this world and the hereafter. This study aims to reveal the mystical ways towards Allah from the perspective of Kyai Sholeh Darat, especially as elaborated in his book Minhāj al-Atqiyā' ilā Ma’rifati Hidāyat al-Adhkiyā' ilā Ṭarīqat al-Auliyā'. This study is qualitative-based research with a descriptive approach. The data were collected from library research. The data were then analysed using the Mile and Huberman analysis. The findings of this study reveal that 1) Kyai Sholeh Darat's book uses references from the Quran, hadith, and the trusted religious texts written by the taṣawwuf scholars; 2) the mystical way or sulūk that a spiritual traveller (sālik) undergoes to get ma'rifatullāh must go through sharī'a, ṭarīqa and ḥaqīqa; and 3) the methods used by Kyai Sholeh Darat in his book are bayānī and irfānī. Contribution: This study affirms that suluk to Allah must go through three paths, namely sharī'a, ṭarīqa and ḥaqīqa. Those three paths cannot be split from one another as there have been movements in which these three aspects are considered separated. For example, to pursue ḥaqīqa, the one only needs ṭarīqa without sharī'a, etc.